Numerical Simulation of Fractional Order Dengue Disease with Incubation Period of Virus: Fractional Order Dengue Disease - Zafar, Zain Ul Abadin; Mushtaq, M.; Rehan, Kashif; Rafiq, M. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Nowadays, numerical models have great importance in epidemiology. These helps us to understand the transmission dynamics of infectious diseases in a very comprehensive manner. In disease epidemiology, vector-host models are important because many diseases are spreading through vectors. Mosquitoes are vectors of dengue disease as these spread the disease in a population. The infectious vectors infect the hosts while infectious hosts infect to vectors .Two main groups of dengue patients are septic and contagious. The susceptible mosquitoes can get dengue infection from infectious humans but not from infected ones. Humans can be categorized into Susceptible, infected, infectious and recovered ones while mosquitoes are susceptible, infected and infectious. Susceptible individual can transfer dengue infection from diseased mosquitoes only. The transmission dynamics of “Fractional order dengue fever” with incubation period of virus has been analyzed in this paper. Using standard methods for analyzing a system, the stability of equilibrium points of the model has been determined. Finally, numerical simulation has been performed for the same problem for different values of discretization parameter ‘h’.